Enhancing the Performance of an HTPE Binder by Adding a Novel Hyperbranched Multi‐Arm Azide Copolyether. Issue 7 (25th March 2020) - Wen, Xiaomu; Zhang, Guangpu; Chen, Keke; Yuan, Shen; Luo, Yunjun
Abstract: Modern composite solid propellants must exhibit excellent mechanical properties together with high energy outputs, and the binder system plays a vital role in establishing these characteristics. In the present work, varying proportions of a novel hyperbranched multi‐arm azide copolyether (POG) were combined with a hydroxyl‐terminated polyether (HTPE) to prepare crosslinked elastomeric binders. The compatibility of the POG and HTPE was demonstrated before a series of HTPE/POG blend binders were prepared based on a urethane reaction using hexamethylene diisocyanate (HMDI) as the curing agent. The mechanical properties of HTPE/POG/HMDI elastomers were found to be superior to those of traditional HTPE/N100 crosslinked binders as a result of the formation of a hyperbranched crosslink structure. Evaluations of the local motions of polymers chains and parameters related to the cured network structure demonstrated the advantages of introducing the hyperbranched POG. Hydrogen bonding in the HTPE/POG/HMDI binder was investigated and the results confirmed that these elastomers also benefited from hydrogen bonding, as well as the entanglement and interpenetration of molecular chains. Decomposition behavior was studied by thermogravimetric analysis, differential thermogravimetry and differential scanning calorimetry, and the new binders exhibited good thermal stability and superior energetic performance that could potentially meet the requirements for military applications. Abstract :